The Design of a Smart Rescue System for Private Swimming Pools - Saleem, Motasim; Abusaimeh, Yazan (Palestine Polytechnic University (PPU) - mechatronics, 2018)
الهدف الأساسي من هذا المشروع هو تصميم وبناء نظام إنقاذ ذكي للمسابح الخاصة يقوم بتحديد موقع الطفل وعملية إنقاذه في حال وقوعه في البركة دون الحاجة الي تدخل بشري، وذلك بإستخدام شبكة حماية تتم عملية رفعها بنظام هوائي ، بالإضافة إلى نظام إستشعار يعمل بالتوازي مع نظام تحكم للتحليل وتحديد موقع تواجد الطفل. عندما يقترب الطفل من البركة دون تواجد شخص بالغ معه، يتم تفعيل المرحلة الاولى من الإنذار كتنبيه اولي ، وعند وصول الطفل لمسافة قريبة جداً من البركة ، يتم تفعيل المرحلة الثانية من الإنذار وتشغيل نظام الحماية لتنبيه الأهل وحماية الطفل من الغرق. The project aims to design and build a smart rescue system for private swimming pools that operates without human assistance. Using a safety rescue net driven by pneumatic system, and a Kinect sensing device associated with a raspberry pi microprocessor for analyzing and sensing. When a child is detected near the pool with no adults around, the first stage alarm is activated. Moreover, when he gets too close to a critical distance from the pool, the second stage alarm, along with the rescue system will be activated, alerting the parents and lifting up the net to the surface.
CD, no of pages 62, 6/2018 ميكاترونيكس, in the store
Keywords: The Design, of a Smart Rescue,System for Private, Swimming Pools